Satisfaction level of patients discharged from a service of Medical Clinic of Paraguay - Real-Delor, Raúl E. (2021)
Introduction: the level of satisfaction in health services is a complex concept that is related to many factors, such as the patient's previous experiences, his lifestyle, expectations regarding treatment and the values of the subject and of society per se. Objectives: to determine the level of satisfaction that patients present upon discharge from the Medical Clinic service of the National Hospital (Itauguá, Paraguay) in 2020. Methods: we perform an observational, descriptive, correlational study. Sample: patients discharged from the Medical Clinic service of the National Hospital in 2020. We included those who could communicate in writing. Those who did not give their informed consent were excluded. Satisfaction was determined with the SERVQUAL questionnaire. Demographic and clinical variables were also measured, as well as functionality with the Barthel scale. The study was approved by the Ethics Committee of the National University of Itapúa (Paraguay). Results: 312 patients entered the study, with a mean age of 47 ± 18 years, being 54% male. The average length of stay was 21 ± 22 days. We found 58% of satisfaction. The Barthel scale showed 49% of some type of dependency. No statistically significant risk factors associated with dissatisfaction were found. Conclusion: the level of satisfaction was high. It is recommended to continue applying quality assessment tools in health care in a systematic and continuous way.